2021
DOI: 10.1097/mao.0000000000003191
|View full text |Cite
|
Sign up to set email alerts
|

Transmastoid Superior Semicircular Canal Plugging: A Prospective Analysis of Surgical Outcomes

Abstract: Objectives: To assess the outcomes of the transmastoid superior semicircular canal plugging in patients with superior semicircular canal dehiscence (SSCD). Study design: Prospective cohort study. Setting: Tertiary, university center. Patients: Patients with SSCD undergoing transmastoid superior semicircular canal plugging within a 30-month period. Interventions: Transmastoid superior semicircular canal occlusion. Main outcome measures: We documented the surgical technique, pre-and postoperative (3-month review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Namely, CHL was restored (<15 dB) in half of the cases, while a residual ABG ≥15 dB could still be detected in half of them. An→ SNHL, either transient or persistent, was detected in a significant number of patients, consistent with data available in the literature [3,[11][12][13][14][16][17][18]22,25,54,55]. Overall, the VEMP threshold normalized and amplitudes decreased, which was consistent with a restoration of the physiological impedance of the inner ear [10,13,21,23,25].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Namely, CHL was restored (<15 dB) in half of the cases, while a residual ABG ≥15 dB could still be detected in half of them. An→ SNHL, either transient or persistent, was detected in a significant number of patients, consistent with data available in the literature [3,[11][12][13][14][16][17][18]22,25,54,55]. Overall, the VEMP threshold normalized and amplitudes decreased, which was consistent with a restoration of the physiological impedance of the inner ear [10,13,21,23,25].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, all patients showed either ipsilesional or contralesional spontaneous nystagmus with variable torsional components in the first days after surgery, which exhibited a spontaneous reversal of direction in the following days in six of the patients, behaving similarly to MD [56]. Even the onset of both SNHL and ipsilesional PSC-BPPV in the post-operative period supports the hypothesis of a transitory perturbation of the whole inner ear, leading to damage to the cochlear hair cells and dislodgement of otoconia from the utricle, respectively [22,54,59]. While HSC-VOR gain fully recovered in all cases, PSC function restored only in some of them.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In 1998, Minor et al (1998) first reported eight cases of SCDS, and since then, many cases of SCDS have been reported (Steenerson et al, 2020;de Wolf et al, 2021;Kontorinis and Gaggini, 2021;Nieto et al, 2021;Ellsperman et al, 2022). The incidence of SCDS is low and its pathogenesis is unknown, and it may be related to head trauma, infection, and pathological changes in the middle ear or adjacent structures (Rosowski et al, 2004;Ward et al, 2017;Mau et al, 2018).…”
Section: Application Of Semicircular Canal Occlusion In Treatment Of ...mentioning
confidence: 99%
“…This usually involves performing a cortical mastoidectomy with preservation of the bony external auditory canal. This is the case, for example, in patients with pulsatile tinnitus who are undergoing surgery to obliterate a sigmoid sinus diverticulum or repair dehiscence over the sigmoid sinus (3) or in patients with intractable benign paroxysmal positional vertigo (BPPV) or superior semicircular canal dehiscence syndrome who undergo transmastoid plugging of the affected semicircular canal (4,5).…”
Section: Introductionmentioning
confidence: 99%